A study on the effect of prolonged mobile phone usage on hearing among students - Srinivasa, V.; Subramaniam, Jayendiran; Chakkravathy, I.; Vel, Harish; Kirushnan, Sathish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Mobile phones have become integral part of our daily life. Since the number of base stations and wireless local area networks increases simultaneously the concern about possible health hazards from exposure to the radiofrequency fields by these wireless technologies also raises. The main aim of our study was to study the effect of prolonged mobile phone usage on hearing among students and to assess the percentage of sensorineural hearing loss among them. Methods: Hundred medical students were enrolled in our study. Basic information was collected from each student using a preliminary questionnaire. All the chronic mobile users who use right ear as the dominant ear were subjected to otoacoustic emissions (OAE) and pure tone audiometry. Results: The OAE results were normal in all the students. We also observed that none of the individuals in our study affected from significant hearing loss (more than 25 dB). But we found a minimal hearing loss in those using mobile phones for more than two hours per day. Conclusions: We concluded that chronic mobile phone usage did not show any significant hearing loss in the study population.